The Developmental Process of Peer Support Networks: The Role of Friendship - Wang, Lingfei; Liang, Lichan; Liu, Zhengguang; Yuan, Keman; Ju, Jiawen; Bian, Yufang (Frontiers in Psychology, 2021)
Peer support is of great importance in the development of adolescents. Adolescents who experience more peer support often report more life satisfaction and fewer psychological problems. Many studies have explored peer support from an individual perspective, such as perceived peer support. Considering the complexity of peer influence within a group, the present study aims to investigate peer support from a group perspective. We employed peer support networks to investigate peer support in classrooms with longitudinal data of Grade 8th and 9th students , and found peer support networks were sparse, hierarchical, and sex-segregated. The formation of new support relationships was influenced by dyadic and triadic support relationships. Additionally, friendships influenced peer support in various ways. Multi-person friendships could improve the formation of support relationships only in one case, implying friendships and other factors (e.g. support resources) work together to affect peer support. The findings proved relationships among adolescents and the interplay between adolescents and the environment would influence their peer support and thus verified ecological systems theory. In summary, peer support is a group process and peer support relationships could be influenced by other members, and then educators and researchers should improve adolescents’ peer support from a group perspective.